Association of change in cognitive function from early adulthood to middle age with risk of cause-specific mortality: the Vietnam Experience Study. Issue 8 (31st May 2019) - Batty, G David; Deary, Ian J; Shipley, Martin J
Abstract : Background: Studies with single baseline measurements of cognitive function consistently reveal inverse relationships with mortality risk. The relation of change in functioning, particularly from early in the life course, which may offer additional insights into causality, has not, to the best of our knowledge, been tested. Aims: To examine the association of change in cognition between late adolescence and middle age with cause-specific mortality using data from a prospective cohort study. Methods: The analytical sample consisted of 4289 former US male military personnel who were administered the Army General Technical Test in early adulthood (mean age 20.4 years) and again in middle age (mean age 38.3 years). Results: A 15-year period of mortality surveillance subsequent to the second phase of cognitive testing gave rise to 237 deaths. Following adjustment for age, a 10-unit increase in cognitive function was related to a reduced risk of death from all causes (HR 0.84; 95% CI 0.75 to 0.93) and cardiovascular disease (HR 0.78; 95% CI 0.64 to 0.95) but not from all cancers (HR 1.14; 95% CI 0.88 to 1.47) nor injury (HR 1.02; 95% CI 0.81 to 1.29). Adjustment for markers of socioeconomic status in middle age resulted in marked attenuation in the magnitude of these associations and statistical significance at conventional levels was lost in all analyses. Conclusions: In the present study, the apparent link between increased cognition and mortality was mediated by socioeconomic status.